The energy recovery of organic waste through anaerobic digestion is an important strategy for reducing greenhouse gas (GHG) emissions and promoting the circular economy in institutional environments. However, the lack of standardized digital tools makes it difficult to systematically record and monitor the operation of educational biodigesters. This paper presents the development and validation of a multi-platform, open-source mobile application for managing biogas production, energy estimates and quantifying avoided emissions in public schools. The system was implemented in Python/Kivy, with a modular architecture and SQLite database for offline operation, including waste registration, automatic calculation of biogas production, monitoring of gas measurements and export of reports. The solution was used in three educational institutions, and a case study was presented in which 219.10 kg of organic waste resulted in an estimated production of 15.12 m³ of biogas and mitigation of 182.10 kg CO₂eq. The results show greater reliability, agility and traceability of operational data, as well as support for environmental management and experimental teaching. The proposed platform is low-cost, scalable and replicable, making it an effective technological tool for integrating renewable energy generation, environmental monitoring and scientific education - Enrique Santacruz Alvarez, Luis; Nunes Maciel, Joylan; Morel Hartmann, Ricardo; Moraes Flores, Diego (Latin American Journal of Energy Research, 2026)
The energy recovery of organic waste through anaerobic digestion is an important strategy for reducing greenhouse gas (GHG) emissions and promoting the circular economy in institutional environments. However, the lack of standardized digital tools makes it difficult to systematically record and monitor the operation of educational biodigesters. This paper presents the development and validation of a multi-platform, open-source mobile application for managing biogas production, energy estimates and quantifying avoided emissions in public schools. The system was implemented in Python/Kivy, with a modular architecture and SQLite database for offline operation, including waste registration, automatic calculation of biogas production, monitoring of gas measurements and export of reports. The solution was used in three educational institutions, and a case study was presented in which 219.10 kg of organic waste resulted in an estimated production of 15.12 m³ of biogas and mitigation of 182.10 kg CO₂eq. The results show greater reliability, agility and traceability of operational data, as well as support for environmental management and experimental teaching. The proposed platform is low-cost, scalable and replicable, making it an effective technological tool for integrating renewable energy generation, environmental monitoring and scientific education
Keywords: biogas; energy management; environmental monitoring; mobile app; sustainability